Evaluasi pelaksanaan belanja modal pada Dinas Perindustrian dan Perdagangan Daerah Provinsi Sulawesi Utara - Balo, Daiyana Natalia; Manossoh, Hendrik; Warongan, Jessy D. L (Universitas Sam Ratulangi, 2020)
Capital expenditure is a government activity that is to add fixed assets with a useful life of more than one fiscal year. Presidential Regulation Number 16 Year 2018 serves as a guideline for each agency as implementing capital expenditure activities. This study aims to evaluate whether the implementation of capital expenditure at the North Sulawesi Provincial Industry and Trade Office is in accordance with regulations. The method used in this research is descriptive analysis method. The results showed that the implementation of capital expenditure at the North Sulawesi Provincial Industry and Trade Office was in accordance with Presidential Regulation No. 16 of 2018 as a standard for implementing capital expenditure and was well planned.